Sodium Arsenite-Induced Learning and Memory Impairment Is Associated with Endoplasmic Reticulum Stress-Mediated Apoptosis in Rat Hippocampus - Sun, Hongna; Yang, Yanmei; Shao, Hanwen; Sun, Weiwei; Gu, Muyu; Wang, Hui; Jiang, Lixin; Qu, Lisha; Sun, Dianjun; Gao, Yanhui (Frontiers in Molecular Neuroscience, 2017)
Chronic arsenic exposure has been associated to cognitive deficits. However, mechanisms remain unknown. The present study investigated the neurotoxic effects of sodium arsenite in drinking water over different dosages and time periods. Based on results from the Morris water maze and morphological analysis, an exposure to sodium arsenite could induce neuronal damage in the hippocampus, reduce learning ability, and accelerate memory impairment. Sodium arsenite significantly increased homocysteine levels in serum and brain. Moreover, sodium arsenite triggered unfolded protein response (UPR), leading to the phosphorylation of RNA-regulated protein kinase-like ER kinase (PERK) and eukaryotic translation initiation factor 2 subunit α (eIF2α), and the induction of activating transcription factor 4 (ATF4). Arsenite exposure also stimulated the expression of the endoplasmic reticulum (ER) stress markers, glucose-regulated protein 78 (GRP78), C/EBP homologous protein (CHOP) and the cleavage of caspase-12. Furthermore, exposure to arsenite enhanced apoptosis as demonstrated by expression of caspase-3 and TUNEL assay in the hippocampus. Results suggest that exposure to arsenite can significantly decrease learning ability and accelerate memory impairment. Potential mechanisms are related to enhancement of homocysteine and ER stress-induced apoptosis in the hippocampus.